2010
DOI: 10.1348/147608309x471000
|View full text |Cite
|
Sign up to set email alerts
|

The experience and meaning of compassion and self-compassion for individuals with depression or anxiety

Abstract: Participants' positive perceptions of self-compassion offer encouragement to clinicians as it appears people can connect with the concept meaningfully as well as seeing it as being useful. Clinicians focusing on self-compassion may gain greater efficacy when they incorporate both aspects within interventions. Findings about the difficulties associated with self-compassion provide valuable information as to why people find it difficult to adopt which can be used in the development of future clinical interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
152
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(168 citation statements)
references
References 19 publications
15
152
0
1
Order By: Relevance
“…As in the nonclinical population [51], being fearful of compassion from others, is highly correlated with being fearful of being self-compassionate (r=.75). This is consistent with qualitative research reporting that depressed individuals find it difficult to imagine receiving compassion from others or being selfcompassionate especially when they are in the state of depression [16,[77][78][79]. So there seems to be a general block and fear of compassion, be it coming from other people or oneself.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As in the nonclinical population [51], being fearful of compassion from others, is highly correlated with being fearful of being self-compassionate (r=.75). This is consistent with qualitative research reporting that depressed individuals find it difficult to imagine receiving compassion from others or being selfcompassionate especially when they are in the state of depression [16,[77][78][79]. So there seems to be a general block and fear of compassion, be it coming from other people or oneself.…”
Section: Discussionsupporting
confidence: 86%
“…For example, further research is needed to understand how these fears operate, how they may vary from person to person, therefore requiring different therapeutic interventions. There is qualitative data to suggest that although depressed patients understand the value of compassion and would like to develop it for themselves, they fear compassion and feel they don't deserve it and are unable to generate or receive it [77]. It could be argued that fears of compassion and affiliative emotions could be treated therapeutically in much the same as any other emotion (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could explore more of this area of study. Neuroticism predicted self-compassion negatively in both samples, supporting past findings of the association of neuroticism in general (krieger et al 2013;neff 2003a;neff et al 2007b;Pauley & mcPherson 2010;PhilliPs & ferguson 2013;raes 2010;shaPira & mongrain 2010;Terry et al 2012). Results showed that self-compassionate seminarians and non-seminarians could experience lower levels of neuroticism.…”
Section: Discussionsupporting
confidence: 84%
“…Each one of these three components has a negative respective value (Self-judgment, Isolation and Over-identification correspondingly). There is a growing number of researchers that link self-compassion to psychological health, while others, relate self-compassion with less anxiety and depression [27,62,63,64]. The Self-compassion questionnaire is comprised of 26 items, from which 6 subscale scores (previously reported) are computed by calculating the mean of subscale item responses.…”
Section: Personality Models Metrics and Other Psychometric Instrumentsmentioning
confidence: 99%